Short-term association between road traffic noise and healthcare demand generated by Parkinson's disease in Madrid, Spain - Julio Díaz; Pablo Martínez-Martín; Carmen Rodríguez-Blázquez; Blanca Vázquez; Maria João Forjaz; Cristina Ortiz; Rocío Carmona; Cristina Linares (Elsevier, 2018)
Objective: To analyse whether there is a short-term association between road traffic noise in the city of Madrid and Parkinson's disease (PD)-related demand for healthcare. Methods: Time-series analysis (2008-2009) using variables of analysis linked to emergency and daily PD-related demand for healthcare (ICD-10: G20-G21), namely, PD-hospital admissions (HAs), PD-outpatient visits (OVs) and PD-emergency medical calls in Madrid. The noise pollution measurements used were Leqd, equivalent sound level for the daytime hours (from 8 a.m. to 10 p.m.), and Leqn, equivalent sound level for night time hours (from 10 p.m. to 8 a.m.) in dB(A). We controlled for temperature, pollution, trends and seasons, and used the Poisson regression model to calculate relative risk (RR). Results: The association between Leqd and HAs was found to be linear. Leqd and Leqn at lag 0.1 and temperature at lags 1 and 5 were the only environmental variables associated with increased PD-related healthcare demand. The RR (lag 0) for Leqd and HA was 1.07 (1.04-1.09), the RR (lag 0) for Leqd and OV was 1.28 (1.12-1.45), and the RR (lags 0.1) for Leqn and emergency medical calls was 1.46 (1.06-2.01). Conclusion: The above results indicate that road traffic noise is a risk factor for PD exacerbation. Measures to reduce noise-exposure levels could result in a lower PD-related healthcare demand. Resumen: Objetivo: Analizar si existe una asociación a corto plazo entre el ruido del tráfico en Madrid y la demanda de asistencia sanitaria por enfermedad de Parkinson (EP). Métodos: Análisis de series temporales (2008-2009) utilizando variables de demanda sanitaria urgente y diaria por EP (CIE-10: G20-G21): admisiones hospitalarias (AH), visitas ambulatorias (VA) y llamadas médicas (112) en Madrid. Los indicadores de ruido fueron Leqd (nivel de ruido diurno equivalente, de 8 a 22 h) y Leqn (nivel de ruido nocturno equivalente, de 22 a 8 h) en dB(A). Se controló por temperatura, contaminación, tendencias y estacionalidades, y se realizó regresión de Poisson para calcular el riesgo relativo (RR). Resultados: La asociación entre Leqd y AH por EP es lineal. Leqd y Leqn en el retardo 0,1 y la temperatura en los retardos 1 y 5, fueron las variables ambientales asociadas con el aumento de la demanda sanitaria. Se obtuvo un RR (lag 0) para Leqd y AH de 1,07 (1,04-1,09), y un RR (lag 0) para Leqd y VA de 1,28 (1,12-1,45). El RR (retardos 0,1) para Leqn y llamadas al 112 fue de 1,46 (1,06-2,01). Conclusión: Los resultados apuntan que el ruido es un factor de riesgo para la exacerbación de la EP. Las medidas para reducir la exposición al ruido podrían dar lugar a una menor demanda de asistencia sanitaria relacionada con la EP. Keywords: Road traffic noise, Parkinson's disease, Hospital admissions, Time series, Outpatient care demand, Palabras clave: Ruido de tráfico, Enfermedad de Parkinson, Ingresos hospitalarios, Series temporales, Demanda de atención médica